2022
DOI: 10.3389/fgene.2022.848951
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity and Selection Signatures for Weining Cattle on the Border of Yunnan-Guizhou

Abstract: Weining cattle is a Chinese indigenous breed influenced by complex breeding and geographical background. The multi-ethnic breeding culture makes Weining cattle require more attention as livestock resources for its genetic diversity. Here, we used 10 Weining cattle (five newly sequenced and five downloaded) and downloaded another 48 genome data to understand the aspects of Weining cattle: genetic diversity, population structure, and cold-adapted performance. In the current study, a high level of genetic diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Commercial breeds/populations with a long breeding history, such as East Asian taurine cattle, European taurine cattle and Eurasian taurine cattle, generally have lower nucleotide diversity. At the same time, the nucleotide diversities of North Chinese cattle breeds are all higher than that of these commercial cattle breeds/populations, which is consistent with previous research results (Guan et al., 2022; Li et al., 2023; Liu et al., 2022; Luo et al., 2022; Mei et al., 2018; Xia, Zhang, et al., 2021). In the North Chinese cattle, the nucleotide diversity of Qaidam cattle is higher than that of the other four breeds.…”
Section: Discussionsupporting
confidence: 90%
“…Commercial breeds/populations with a long breeding history, such as East Asian taurine cattle, European taurine cattle and Eurasian taurine cattle, generally have lower nucleotide diversity. At the same time, the nucleotide diversities of North Chinese cattle breeds are all higher than that of these commercial cattle breeds/populations, which is consistent with previous research results (Guan et al., 2022; Li et al., 2023; Liu et al., 2022; Luo et al., 2022; Mei et al., 2018; Xia, Zhang, et al., 2021). In the North Chinese cattle, the nucleotide diversity of Qaidam cattle is higher than that of the other four breeds.…”
Section: Discussionsupporting
confidence: 90%
“…This result may be related to the continuous provision of energy for pigs to resist the cold. Some studies found that UBE3D had a relationship with fat composition in sheep, and it was a cold-resistant candidate gene in Weining cattle [ 42 , 43 ]. Therefore, UBE3D may be related to the adaptation of pigs to low temperatures in the northern region.…”
Section: Resultsmentioning
confidence: 99%
“…Major risks include genetic erosion and the loss of breed-specific genetic variation. It is commonly recognized that local cattle, such as those from Bali, have a significant number of favorable features, including the capacity to withstand hot weather conditions, poor fodder quality and resistance to internal parasites and infectious illnesses (Mohamad et al, 2012;Bakae et al, 2022;Liu et al, 2022;Trujano-Chavez et al, 2022;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%